Treatment of ineffective endocardial defibrillation with subcutaneous array: a case report - Özgür Kaplan; Sabri Demircan (Türk Kardiyoloji Derneği Arşivi, 2017)
Defibrillation threshold (DFT) testing is an important part of ICD implantation. After placement of the ICD generator, a DFT test is performed to evaluate the integrity of the ICD system and to confirm a successful defibrillation safety margin. More than 6% of ICDs implanted are not within the DFT safety margin. Presently described is the case of a patient with a high DFT and some of the methods that can be used to manage this circumstance, including the use of a subcutaneous array.